VKP(V) CK politbiuro and sovietisaton of annexed territories in 1939–1941 - Lebedeva, Natalija (Genocidas ir rezistencija, 2000)
Protocols of the Communist Party of the Soviet Union Central Committee politburo, also documents of the territorial organizations of Communist Party reflect tragical situation of occupied in 1939–1941 territories and dramatic changes. This paper reflects how processes of incorporation, sovietisation of occupied territories was organized, what were similarities and differences of sovietisation of territories occupied in 1939–1941, and what was so special of sovietisation implemented by J. Stalin government.